2017
DOI: 10.1093/mnras/stx2029
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from SN 2012ca: A Type Ia-CSM supernova explosion in a dense surrounding medium

Abstract: X-ray emission is one of the signposts of circumstellar interaction in supernovae (SNe), but until now, it has been observed only in core-collapse SNe. The level of thermal X-ray emission is a direct measure of the density of the circumstellar medium (CSM), and the absence of X-ray emission from Type Ia SNe has been interpreted as a sign of a very low density CSM. In this paper, we report late-time (500-800 days after discovery) X-ray detections of SN 2012ca in Chandra data. The presence of hydrogen in the ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…An immediate method to probe circumstellar gas is through X-ray observations, and the only SNIa detected in X-rays is SN2012ca (Bochenek et al 2017). This SN belongs to the class of SNIa Hα emitters, and the mass of the circumstellar shell is at least 0.1±0.05 M  .…”
Section: Circumstellar Emission and Interactionmentioning
confidence: 99%
“…An immediate method to probe circumstellar gas is through X-ray observations, and the only SNIa detected in X-rays is SN2012ca (Bochenek et al 2017). This SN belongs to the class of SNIa Hα emitters, and the mass of the circumstellar shell is at least 0.1±0.05 M  .…”
Section: Circumstellar Emission and Interactionmentioning
confidence: 99%
“…Until very recently no type Ia SN explosion has been confirmed in X-rays, but Bochenek et al (2018) have reported the detection in Chandra data of SN 2012c, a type Ia-CSM object, i.e., a type Ia SN surrounded by very dense material. On the other hand more than 60 core-collapse SNe have been detected in X-rays (see Ross & Dwarkadas 2017, and the SNaX database at http://kronos.uchicago.edu/snax/).…”
Section: X-ray Facilitiesmentioning
confidence: 99%
“…Many progenitor classes have been proposed (Gilfanov et al 2010, Wang & Han 2012, Maoz 2014, but observational evidences have not yet reached definitive conclusions on particular progenitor systems. The SD scenario is favored by the possible detections of circumstellar materials (CSM) around some SNe Ia through detections of strong ejecta-CSM interaction (Hamuy et al 2003, Wang et al 2004, Aldering et al 2006, Taddia et al 2012, Silverman et al 2013, Bochenek et al 2018 or evolving narrow absorption lines possibly due to CSM (Patat et al 2007, Sternberg et al 2011, Dilday et al 2012, while there are also observational findings suggesting no companion signatures for some SNe Ia (Li et al 2011a, Gonzalez et al 2012, Schaefer et al 2012, Olling et al 2015. This may suggest that SNe Ia have multiple progenitor systems, as favored by the discovery that SNe Ia with different ejecta velocities originate from distinct birthplace environments .…”
Section: Introductionmentioning
confidence: 99%